Ethics as it appears in the Singkalakasutta - Phuengphai, PhraSuriyon Narissaro; Haohan, PhraPhaithun Chantakamo; Pongpha, Paisin; Khammuangsaen, Boonruam (Journal of Dhamma for Life, 2025)
From the study, it was found that the principles in Singkalakasutta which consist of 4 kamma defilements, 4 biases, 6 vices, false friends, true friends and 6 directions. When people put them into practice, they will make their lives within the framework of morality, be a good person, be able to live peacefully with others in society. They were a generous to others, love peace, respect each other, and do not cause harm to each other.